?ENVIRONMENTAL IMPACT ASSESSMENT OF AIR POLLUTION IN DIFFERENT AREAS OF KARACHI (Biological Sciences - PJSIR, 2003)
Measurements of major ambient air pollution components such as O3, SO2, CO, NO, and NOx were carried out to obtain baseline data for some selected areas in Karachi. These areas have been categorized on the basis of traffic congestion. Total average concentration of O3 in Zone - A was 20.80 ppb. In Zone - B 20.36 ppb and in Zone - C 19.10 ppb. Concentration of SO2 in Zone - A was determined to be 7.30 ppb, in Zone - B 11.60 ppb and in Zone - C 44.30 ppb. Similarly, concentration of CO in Zone - A was 0.96 ppm, in Zone - B 2.50 ppm and in Zone - C 3.49 ppm. Whereas, average concentration of NO and NOx was 13.00 ppb and 23.50 ppb in Zone - A, 2.73 ppb and 5.70 ppb in Zone - B, 69.90 ppb and 83.50 ppb in Zone C. The main contributors of pollutants in these areas are vehicular traffic and industries. A survey of local hospitals was also conducted to correlate the prevailing diseases with air pollution levels. The survey showed that 70% of the patients were suffering from air pollution related diseases, like chronic bronchitis, pulmonary edema and pulmonary emphysema. The data further reveals that the ratio of male to female patients is 2:1.